PERBANDINGAN KUALITAS CITRA PADA TIGA SOFTWARE VIDEO - -, Harmastuti; Setyowati, Dwi; Prasetyo, Panggih Cahyo; Widhiatmoko, Mahendra Kurnia (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2019)
The development of information technology is currently very rapid, can be seen in the real world how important the use of video, such as in the field of advertising, entertainment, business and no less important in the field of education for the delivery of learning information which all require a clear and attractive display. In this study, we will examine a comparison of three video software on image quality, image sharpness, brightness and audio effects in Windows Live Movie Maker, VideoSpin and Movavi Video. The research conducted made the video using the three software on the NTSC video format, AVI file type, resolution (720x480), 4:3 Pixel ratio, Standard D1 aspect ratio (0.09), 1500 kbps bit rate, 29.97fps frame rate with Audio: Stereo Channels, 48,000 HZ sample rate, 2.2 minutes duration. The samples were taken by the HMJ activities (HIMAKOM), namely graphic science competitions, sports, the introduction of new software training students, data used by static photos. For testing, questionnaires were collected on 43 respondents, students, majoring in Computer Systems and Statistics to assess the results of the video from the three video software and then tested with Anova to find out which one was better. From the results of the calculation of respondents' data, the average respondents liked the Movavi Video software with an image quality value of 89.2, sharpness of images 88.103, audio effects 83.333 and after being tested using Anova software Movavi Video analysis was better. It was concluded in this study that Movavi Video software could be a consideration to choose from in making videos.